2002
DOI: 10.1110/ps.0222102
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the enhanced thermal stability of alcohol dehydrogenase mutants from the mesophilic bacterium Clostridium beijerinckii: contribution of salt bridging

Abstract: Previous research in our laboratory comparing the three-dimensional structural elements of two highly homologous alcohol dehydrogenases, one from the mesophile Clostridium beijerinckii (CbADH) and the other from the extreme thermophile Thermoanaerobacter brockii (TbADH), suggested that in the thermophilic enzyme, an extra intrasubunit ion pair (Glu224-Lys254) and a short ion-pair network (Lys257-Asp237-Arg304-Glu165) at the intersubunit interface might contribute to the extreme thermal stability of TbADH. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 82 publications
(135 reference statements)
0
35
0
3
Order By: Relevance
“…On the other hand, proline composition increased significantly, which might be the structural base of the rigidity of hyperthermophilic enzymes (23). The difference between hyperthermophilic and mesophilic proteins/enzymes would provide clues for increasing the thermal stability of mesophilic enzymes (8,9). The physiological role of T. guaymasensis ADH seems not to be clearly ascertained, simply relying on its conserved domain homology to threonine dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, proline composition increased significantly, which might be the structural base of the rigidity of hyperthermophilic enzymes (23). The difference between hyperthermophilic and mesophilic proteins/enzymes would provide clues for increasing the thermal stability of mesophilic enzymes (8,9). The physiological role of T. guaymasensis ADH seems not to be clearly ascertained, simply relying on its conserved domain homology to threonine dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in the thermophilic glutamate dehydrogenase that ion pair networks provide more stability to the protein molecules than isolated ion pairs, and this phenomenon is particularly effective at higher temperatures [34]. The role of salt bridges in the thermal stability of TBADH was demonstrated earlier by Bogin et al [21]. In addition, disruption of an ionic network around Arg20 accelerates the unfolding rate in D-glyceraldehyde-3-phosphate dehydrogenase [35].…”
Section: Discussionmentioning
confidence: 88%
“…We performed an additional search for salt bridges, using a structure with a slightly higher resolution than in the earlier work (PDB id 1YKF) with the Web version of the WHAT IF software, which revealed 14 intermolecular salt bridges. Indeed, a role of ionic networks for thermal stability has been demonstrated [21]. A closer examination of the structural determinants showed that they are strategically placed at the subunit interface (e.g., Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ikura and coworkers have shown that there are important water-mediated interactions at the barnase-barstar protein-protein interface (Ikura et al, 2004). Additional research into the significance of water mediated interactions have shown that engineered ion pairs from a protein found in a thermophile when introduced into an homologous protein from a mesophilic bacterium lead to additional water mediated interactions and enhanced stability (Bogin et al, 2002). Another study showed that a new water mediated interaction was present for a protein at lower temperature suggesting the plasticity of ion pairs in proteins (Natesh et al, 2003).…”
Section: Thermal Stability and Oligomerization Statementioning
confidence: 99%